Insights into the Role of Extracellular Polysaccharides in Burkholderia Adaptation to Different Environments - Ferreira, Ana S.; Silva, Inês N.; Oliveira, Vítor H.; Cunha, Raquel; Moreira, Leonilde M. (Frontiers in Cellular and Infection Microbiology, 2011)
The genus Burkholderia comprises more than 60 species able to adapt to a wide range of environments such as soil and water, and also colonize and infect plants and animals. They have large genomes with multiple replicons and high gene number, allowing these bacteria to thrive in very different niches. Among the properties of bacteria from the genus Burkholderia is the ability to produce several types of exopolysaccharides (EPSs). The most common one, cepacian, is produced by the majority of the strains examined irrespective of whether or not they belong to the Burkholderia cepacia complex (Bcc). Cepacian biosynthesis proceeds by a Wzy-dependent mechanism, and some of the Burkholderia cepacia exopolysaccharide (Bce) proteins have been functionally characterized. In vitro studies showed that cepacian protects bacterial cells challenged with external stresses. Regarding virulence, bacterial cells with the ability to produce EPS are more virulent in several animal models of infection than their isogenic non-producing mutants. Although the production of EPS within the lungs of cystic fibrosis (CF) patients has not been demonstrated, the in vitro assessment of the mucoid phenotype in serial Bcc isolates from CF patients colonized for several years showed that mucoid to nonmucoid transitions are relatively frequent. This morphotype variation can be induced under laboratory conditions by exposing cells to stress such as high antibiotic concentration. Clonal isolates where mucoid to nonmucoid transition had occurred showed that during lung infection, genomic rearrangements and mutations had taken place. Other phenotypic changes include variations in motility, chemotaxis, biofilm formation, bacterial survival rate under nutrient starvation and virulence. In this review, we summarize major findings related to EPS biosynthesis by Burkholderia and the implications in broader regulatory mechanisms important for cell adaptation to the different niches colonized by these bacteria.